Sub-Block Approach Technique for Improving the Localization Resolution of the Fragile Watermarks - Erturkler, Metin; Tatar, Yetkin (Gazi Univ, 2008)
In this paper, a fragile watermarking technique having both secure against attacks and high accuracy determination of tampered region independent from image resolution was presented for image authentication. In the proposed technique, a dividing structure named sub-block structure, a dependency order constituted on this structure and an algorithm employing this dependency order were developed. Furthermore, a superior trade-off between security and tamper localization of the technique was provided by means of using two different signature algorithms together.
Keywords: Digital watermarking; authentication; localization resolution